Is there a future for livestock in a sustainable food system? Efficiency, sufficiency, and consistency strategies in the food-resource nexus - Isabel Jaisli; Gianluca Brunori (Journal of Agriculture and Food Research)
Livestock production has been identified as the most relevant factor for the sustainability of future food system and is anticipated to be increasingly influenced by competition for critical resources such as land and water, the rivalry between food and feed, and the imperative to function within a carbon-constrained economy. In this context, our review synthesizes insights from 88 peer-reviewed articles, analysing measures aimed at steering future livestock production towards sustainability. Three distinct pathways emerge: the efficiency pathway, encapsulating sustainable intensification; the consistency pathway, encompassing circularity and grassland-based systems; and the sufficiency pathway, embodied by the protein transition. While some aspects along these strategies are aligned with each other, these pathways are also often contradictory and associated with a range of trade-offs. The results underscore the importance of considering regional variations and diverse production systems in selecting optimal strategies for future livestock management. Overall, a nuanced understanding of these pathways is crucial for informed decision-making in shaping a sustainable and resilient future for livestock and the planet.